Soft-Decision Decoding of Permutation-Based Optical Codes for a Multiple Access System; IEEE Communications Letters; Vol. 25, iss. 9 - Mulundumina Shimaponda-Nawa; Oluwafemi Kolade; Wenbo Ding; Dzhayakodi (Jayakody) Arachshiladzh D. N. K. Dushanta Nalin Kumara; Ling Cheng (2021, 2021)
Title screen